A CAD-interfaced dynamics-based tool for analysis of masonry collapse mechanisms. (1st October 2018) - Mehrotra, Anjali; DeJong, Matthew J.
Highlights: A CAD-based tool for dynamic analysis of masonry collapse mechanisms is presented. Geometrically complex structures and collapse mechanisms are considered. The tool allows for interactive graphical definition of the collapse mechanisms. The results are compared to experimental tests and field observations. The tool is demonstrated by assessing the seismic capacity of two case studies. Abstract: This paper presents a new CAD-interfaced analytical tool for the nonlinear dynamic analysis of masonry collapse mechanisms. Utilizing rocking dynamics, the tool derives and solves equations of motion for a broad range of collapse mechanisms, for any user-defined structural geometry. Using as a starting point a digital drawing of the structure in Rhino (a typical CAD software), the tool computes the kinematic constants defining these equations of motion, which are then exported to MATLAB and solved for either pulse-response to generate overturning spectra, or full time-histories. The use of the tool is demonstrated by comparing its predictions to results from experimental shake-table tests, as well as against field observations from the 2015 Gorkha earthquake, while its predictive abilities are illustrated using as case-studies the Casa Grande Ruins National Monument in the United States, as well as the Church of San Leonardo Limosino in Italy, which sustained some damage during the 2012 Emilia earthquake sequence.